Adverbes, adverbiaux et coverbes : pour compléter une réflexion commencée avec Estelle Moline - Cyril Aslanov (Studii de Lingvistica)
This article aims at perceiving to which extent the Italic adverb has innovated with respect to the Proto-IndoEuropean legacy. This leads us to the issue of the adverb considered from a typological perspective and of the status of the adverb in some languages where the adverbial system is quite different from that of the Indo-European languages. I will examine among others the question of the coverb that is functionally equivalent to an adverb from a semantic point of view although it belongs without doubt to another part of speech, that of the verb. I will also deal with the sometimes-difficult distinction to be made between adverbs and prepositions (or postpositions). Lastly, the modal particle could corroborate the impression that the adverb often transcends the boundaries between the parts of speech.